BIOM-07. LOW EXPRESSION OF HLA-A AS A NOVEL PROGNOSTIC FACTOR IN GLIOBLASTOMA TREATED WITH TUMOR FUSED DENDRITIC CELL VACCINES. (14th November 2022) - Takei, Jun; Akasaki, Yasuharu; Tanaka, Toshihide; Fukasawa, Nei; Gomisawa, Kazutaka; Satake, Mari; Mori, Ryosuke; Yamamoto, Yohei; Oda, Ayaka; Kamata, Yuko; Murahashi, Mutsunori; Fukuda, Takahiro; et al.
Abstract: Although immunotherapy has become an attractive approach to cancer treatment in patients with broad types of aggressive tumors, phase III clinical trials of immunotherapy for glioblastoma (GBM) have not achieved extended survival of patients. Dendritic cells perform an essential role in the immune system as antigen-presenting cells and tumor fused dendritic cells (TFDCs) can induce tumor-specific cytotoxic T cells as a cancer vaccine. We have previously described the safety and mechanisms of TFDCs therapy, as well as immunological and clinical responses of patients with GBM, however, there were little known about predictive and prognostic biomarkers specific to TFDCs therapy. In the present study, we investigated the whole transcriptome sequencing of tumor cells, and novel prognostic factors were identified through molecular profiling GBM treated with TFDCs immunotherapy. Fifty-three patients were eligible in this study and 28 samples from patients with newly diagnosed GBM IDH wild-type were included. Of these 28 samples, 15 high-quality RNA samples successfully extracted from tumors were analysed. The samples were divided into two groups based on the median patient's overall survival. Differential expression analyses and enrichment analysis between the two groups were carried out using CLC Genomics Workbench (QIAGEN), and Gene Ontologies (GO) were assigned. A total of 473 differentially expressed genes were detected including 327 enriched GO terms. Fifteen GO terms out of 327 GO terms represented the highest enrichment scores, revealed that five GO terms were associated with the major histocompatibility complex (MHC). The relationship among the MHC, immune-related genes, and clinical outcomes was investigated using the Cox regression model and Kaplan–Meier log-rank test. Low expression of HLA-A in the tumors turned out to be a significantly favorable prognostic impact (p = 0.01). The decreased expression of HLA-A might be a novel prognostic factor in GBM patients treated with TFDCs immunotherapy.